PROFESIONALISME POLRI DALAM PENERAPAN WEWENANG DISKRESI DALAM KASUS TINDAK PIDANA PENCURIAN (STUDI KASUS PENCURIAN KAKAO, PENCURIAN BIJI KAPUK, DAN PENCURIAN SEMANGKA) - Iqbal Felisiano; Amira Paripurna (Universitas Airlangga, 2010)
Police discretion by definition is the power to make decisions of policy and practice. Police have the choice to enforce certain laws and how they will be enforced. Discretion is bounded by norms (professional nor ms, community norms, legal norms, moral norms). Officers will exercise discretion in situations here the facts or people involved don not necessarily line up with the law. Discretion is exercised far more in speeding cases, vandalism, domestic violence or juvenile cases rather than homicide, rape case, thievery, robbery. Officers often feel minor offenses are more about educating citizens, whereas serious offenders deserve the full punishment of the law. If a police officer uses his/her discretionary power correctly, not only will it help the police officer in their situation, it will help the general community as well.Key words : discretion, police officer